Diretrizes de educação de usuários para bibliotecas universitárias federais brasileiras em período pandêmico - Silva, Larissa Fernandes da (2024)
Duringthe Covid-19 pandemic, weexperiencedsignificantchanges in thewayday-todayactivitieswereconducted, mainlyduetothenecessary social isolationtoreducetheriskofcontamination. Severalprofessionalshadtoperformtheirfunctions in the online environment, includinglibrarians. Giventheseevents, some questionsthat gave risetotheresearch: “Howwere User Educationactivitiesdeveloped in Brazilian federal universitylibrariesduringthe Covid-19 pandemicperiod? What are thedifficultiesfacedbylibrarians in developingsuchactivities?” Seekingtofindanswerstosuchquestions, the general objectiveoftheresearchwastoanalyzehow User Educationdeveloped in Brazilian federal universitylibrariesduringthepandemicperiod. As for themethodology, it is anexploratoryanddescriptivestudy, with a mixed approach. The researchuniversitiesthe central librariesof federal universities in Brazilandthe data collectioninstrumentconsistedof a questionnaire thatisdividedintothreeparts: thefirstaboutthe profile oftherespondents, thesecondaboutthelibrary in whichthelibrariansworked,andthe third part aboutreferenceserviceon User Education. Thisinstrumentwascreated in Google formsandappliedtothereferencelibrariansoftheselibraries. For theanalysisofquantitative data, statisticalcalculationswereused, and for qualitative data, Bardin'sContentAnalysiswasadopted. Aimingtodelimittheresearchuniverse, a searchwascarried out ontheMinistryofEducation (e- MEC) portal toidentifythenumberof federal universities in the country, and, usingthefilterthatdefinedthosewithaninstitutionalconceptequaltoorgreaterthan 04, resulted in 44 federal universities, thatis 44 libraries. The questionnairewassenttotheselibraries, receiving feedback from 31 participants. The researchresultsdemonstratedthatlibrarians, despitethedifficultiesfacedandreported in the open questions, in additiontotheabruptchangetotrytodeliverservices online, werecommittedto meeting theneedsoftheirusersthrough training, qualifications, video lessons, use of social networks and digital platformsbothtoapplysuchinstructionsand for otherservices. It isconcludedthatlibrariesneedtohave a direction, thatis, theyneedguidelines for optimizingtheirservicesduring a pandemicperiod, as well as actuallydeveloping user educationprogramsthrough a committeeformedbylibrarians in orderto make theircompetentinformationusers.